Pengaturan asas keterbukaan dalam pembentukan undang-undang - Angga Prastyo; Samsul Wahidin; Supriyadi Supriyadi (University of Merdeka Malang, 2020)
This legal research is based on the focus of the problem regarding the Regulation of the Principle of Openness of Law Formation in Indonesian Positive Law, and the Regulation of the Principle of Openness of Correct Formation of Laws in Indonesian Positive Law. This research includes normative legal research with a statutory approach and in the analysis of legal materials using qualitative descriptive techniques. Based on the results of research and analysis of problems in this study, it is concluded that the Regulation of the Principle of Openness of Law Formation in Indonesian Positive Law contains provisions that underlie the availability of information on the implementation of Law Formation for all elements of society, but not as a whole, and the Regulation of the Principle of Openness In the Formation of Laws in accordance with the Positive Law of Indonesia are the arrangements that underlie the availability of information on the Formation of Laws that are disseminated and conveyed transparently to the public, as well as the widest possible opportunity for all elements of society to provide input in the Formation of Laws in accordance with with the Principles of Formation of Laws and General Principles of Good Governance.How to cite item: Prastyo, A., Wahidin, S., Supriyadi, S. (2020). Pengaturan asas keterbukaan dalam pembentukan undang-undang. Jurnal Cakrawala Hukum, 11(2), 125-135. doi:https://doi.org/10.26905/idjch.v11i2.4136